Elevated Neutrophil to Lymphocyte Ratio Predicts Poor Prognosis in Non-muscle Invasive Bladder Cancer Patients: Initial Intravesical Bacillus Calmette-Guerin Treatment After Transurethral Resection of Bladder Tumor Setting - Yuk, Hyeong Dong; Jeong, Chang Wook; Kwak, Cheol; Kim, Hyeon Hoe; Ku, Ja Hyeon (Frontiers in Oncology, 2019)
The study investigated the pretreatment systemic inflammatory response (SIR) markers of patients who underwent initial intravesical treatment for high-risk non-muscle invasive bladder cancer (NMIBC).385 patients who underwent initial intravesical Bacillus Calmette-Guerin treatment after transurethral resection of bladder tumor were included. We analyzed the relationship between ratio of SIR markers, such as neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocyte ratio (dNLR) and platelet-to-lymphocyte ratio (PLR), and oncological outcomes. Each SIR marker was used for analysis by determining the cut-off value through receiver operation characteristics curves analysis. Patients were divided into two groups according to pretreatment NLR (<1.5 vs ≥1.5), dNLR (<1.2 vs ≥1.2) and PLR values (171<vs ≥171). Patients with NLR≥1.5, dNLR≥1.2 were associated with poor prognosis in terms of overall survival and cause-specific survival. However, no serum SIR markers were associated with prognosis in regression-free survival and progression-free survival. Cox multivariate analysis revealed that age. NLR, dNLR, hemoglobin, and pathologic T stage were important factors for predicting overall survival. Age, NLR, and pathologic T stage were important factors for predicting cancer-specific survival, NLR and tumor number were the most important predictors of bladder preserving survival. NLR before treatment was correlated with both oncological outcomes and survival outcome in NMIBC patients undergoing initial intravesical BCG treatment after TURB. Increased NLR reflects a poor prognosis of these outcomes.